Hukum Dan Konsumen Remaja (Studi Tentang Perlindungan Hukum Terhadap Acara Reality Show di Televisi) - Bachtiar, Bonno; , Dr. Kelik Wardiono, S.H., M.H (2016)
Television can be a positive effect if it can be consumed wisely and used it well, such as expanding the insight. Television can also be a negative effect if the teenager or the audience can not filter out the positive things of what the watch. One example of the negative effect teenager watching television is feeling too confident and his emotions rise makes it difficult to accept the advice of his parents. Often the audience of television (in this case teenager) always in the spotlight because of his behavior in front of the television. A teenager actually is the phase where a person is experiencing a rising phase in his life, or rather being in puberty. In the reality show, a lot of things could be revealed, including aspect of honesty and willingness to help others. However, this guys impressions can cause bad effect that may never estimated by the maker and television that relay it.